Շեղված հաբիտուսը (Թոմաս Մանի օրինակը) - Սիմյան, Տիգրան (YSU Journal of International Affairs, 2014)
This article focuses on antimilitaristic discourse studies based on the example of the "Reflections of a Nonpolitical Man" by T. Mann. Particular attention is paid tothe analysis of such oppositions used by the author as spirit / politics, culture / civilization, soul / society, arts / literature, cosmopolitanism / internationalism, German spiritual values, humanity / bourgeois democrat, etc. The author of the article also critically analyzes the articles of such Russian thinkers as Vladimir Ern and Sergei Bulgakov. After the assassination of the Foreign Minister Walter Rathenau (1923), Thomas Mann rethought his own political views and became an ardent pacifist. In the article the axiological "revolution" of Mann’s ideas is demonstrated on the basis of a few examples of his reports, essays and articles ("My Time", "Culture and Politics", etc.).
Keywords: pacifism, militarism, habitus of intellectual, axiological war,